2023
DOI: 10.1007/s00374-023-01722-8
|View full text |Cite
|
Sign up to set email alerts
|

Does liming improve microbial carbon use efficiency after maize litter addition in a tropical acidic soil?

Abstract: Soil pH is one of the main drivers of soil microbial functions, including carbon use efficiency (CUE), the efficiency of microorganisms in converting substrate C into biomass, a key parameter for C sequestration. We evaluated liming effects after maize-litter addition on total CUE (including microbial residues), CUE of microbial biomass (CUEMB), and fungal biomass on an acidic Acrisol with a low C. We established a 6-week incubation experiment to compare limed and unlimed Acrisol treatments and a reference soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Rousk et al proposed that low pH values can reduce microbial indicators of soil quality, such as fungi, bacteria, and microbial biomass and, to a lesser extent, reduce microbial activity without affecting metabolism [ 52 ]. Fungi in soil have a strong tolerance for acidification, and Moran et al’s research has shown that fungal biomass is not affected by pH values [ 53 ]. Therefore, the changes in fungal biomass are not as significant as those in bacteria, and the abundance of some acidophilic microbial populations changes significantly, disrupting the distribution balance between bacterial and fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Rousk et al proposed that low pH values can reduce microbial indicators of soil quality, such as fungi, bacteria, and microbial biomass and, to a lesser extent, reduce microbial activity without affecting metabolism [ 52 ]. Fungi in soil have a strong tolerance for acidification, and Moran et al’s research has shown that fungal biomass is not affected by pH values [ 53 ]. Therefore, the changes in fungal biomass are not as significant as those in bacteria, and the abundance of some acidophilic microbial populations changes significantly, disrupting the distribution balance between bacterial and fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Marie et al [11] suggested that soil amended with N benefited from both an increase in the residual C absorbed by the microbes and a reduction in the SOC loss triggered by the PE when compared with soil under conditions of limited N. Additionally, a significant negative relationship between CUE and the PE under low-N treatment conditions was recently reported [14,15]. N fertilizer can increase the CUE by decreasing the stoichiometric C-to-N imbalance [13][14][15][16]. Many researchers have noted that CUE not only represents residual C utilization, but it also is associated with SOC accumulation and long-term C stabilization [9,17], because a positive relationship between SOC sequestration and CUE has been found [13,18].…”
Section: Introductionmentioning
confidence: 97%
“…Soil N availability is a dominant factor driving microbial CUE. For example, Marie et al [11] suggested that soil amended with N benefited from both an increase in the residual C absorbed by the microbes and a reduction in the SOC loss triggered by the PE when compared with soil under conditions of limited N. Additionally, a significant negative relationship between CUE and the PE under low-N treatment conditions was recently reported [14,15]. N fertilizer can increase the CUE by decreasing the stoichiometric C-to-N imbalance [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation